Política de formação docente no Brasil: uma análise do PIBID Unioeste campus Cascavel - PR - Paulo, Marcio Issler (2018)
Considering the theor etical and political aspects present in the Scholarship Programs for Beginner Teachers (PIBID), the current paper aims to present a panoramic view of the Teachers Education Policy in Luis Inácio Lula da Silva (2003 - 2010), and Dilma Rousseff (2014/Michel Temer) government, regarding to understand the moviments that are intertwined in a contradictory way in the current reality, as remnants of the previous governments. In relation to the PIBID, as na educational policy for teacher seducation, we seek to analyzeifthe policies that support the program explain some doctrine, thusunderlining a the oreticaland political-pedagogical orientation; how the PIBID was implemented at UNIOESTE Cascavel campus, in order tounderstand the ways, the limits, the existing contradictions, as well as the meanings that are produced by this policy focused on teachers education. In methodological terms for the realization of this research we will firstest ablish the accomplishment of a bibliograp hicre search, ming besides the definition of themost important concepts, the necessary basist o the ful fillmento the first objectives. The before, the theoretical-methodological consideration swere guided through “the political-cycle approach”by Stephen Ball, who chis opposed to a traditional analysis. This approach is in tended to understand the structuring movement scarried out by the policy, identifying the element that constituteit so that we can understand eachoftho se elements particular lyrelated to the historical conjuncture materialisati on of Brazilian public educational policy. As in instrument of data collection for the accomplishment of this research semi-structured interviews were used, as well as a structured questionnaire, hosted on Google Forms platform, through na access link. For the analisy sof the obtained data, the oreticaland political aspects were considered whichin fluenced in a director indirect manner the objective of this work, thus allowing to discuss the practical work conditions that directly influence in the program effectiveness.